2019
DOI: 10.1016/j.ijrmms.2019.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Fracturing evolution analysis of Beishan granite under true triaxial compression based on acoustic emission and strain energy

Abstract: The study of rock fracturing is a fundamental research in rock mechanics and engineering. In this paper, based on the complete stress-strain curves under TTC, the corresponding AE and strain energy results, the mechanical properties and fracturing process of the Beishan granite are studied.A representative test result (σ2=75 MPa, σ3=20 MPa) is selected to analyse and illustrate the three-dimensional fracturing process of the Beishan granite. The results show that the variations in the brittle fracture behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…This indicates that the rock weaks with water content, which increases the internal damage and ultimately reduces the dissipation strain energy rate. In other words, the higher the strength more will be the dissipation strain energy rate and vice versa [72][73][74][75][76][77][78][79].…”
Section: Strain Energy Ratementioning
confidence: 99%
“…This indicates that the rock weaks with water content, which increases the internal damage and ultimately reduces the dissipation strain energy rate. In other words, the higher the strength more will be the dissipation strain energy rate and vice versa [72][73][74][75][76][77][78][79].…”
Section: Strain Energy Ratementioning
confidence: 99%
“…To simulate the stress path of rock mass failure in deep underground engineering, the typical stress path (Zhang et al, 2019) finally adopted in this study is shown as follows: (a) Hydrostatic loading stage: loading simultaneously in three principal stress directions (σ 1 = σ 2 = σ 3 ) at a loading rate of 0.5 MPa/s to the minimum principal stress level. (b) Intermediate principal stress loading stage: keeping σ 3 unchanged and loading σ 1 and σ 2 simultaneously (σ 1 = σ 2 ) at a loading rate of 0.5 MPa/s to set the σ 2 level.…”
Section: Failure Analysis Of Granite Sample Based On True Triaxial Testmentioning
confidence: 99%
“…Early uniaxial rock mechanics test (Zhao and Jiang, 2010) have evolved into a true triaxial excavation simulation, including the installation of various monitoring instruments to observe the rockburst process (He et al, 2012), analyze the shape and kinetic energy of rockburst blocks (Su et al, 2017a;Su et al, 2017b), and study the acoustic emission spectrum characteristics, energy release , and rockburst tendency (Gong et al, 2020). (Zhang et al, 2019a;2019b;2019c;Zhang et al, 2021) proposed a strain energy determination method for rocks under true triaxial compression (TTC), and investigated the energy evolution process and mechanism of different hard rocks under true triaxial compression (TTC) using strain energy analysis (Qu et al, 2022). In order to accurately and effectively predict the occurrence of rock bursts, a multi-indicator evaluation method for the occurrence of rock bursts at deep subsurface rock openings was established (Xu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%